EFFECT OF TIROFIBAN ON THE OUTCOME DURING HOSPITALIZATION IN PATIENTS WITH ACUTE CORONARY SYNDROME AN OBSERVATIONAL STUDY - K, Thamayanthi; Ranganathan, Arun; K, Vasanthira (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was intended to know the effect of tirofiban on the prognostic outcome of patients with acute coronary syndrome (ACS) during their stay in the hospital. Methods: Registers and case sheets of patients admitted for ACS during May 2014–April 2015 were analyzed retrospectively. The duration of stay in hospital/Intensive Care Unit (ICU) and the outcomes were recorded in patients who received tirofiban. ACS patients who did not receive tirofiban served as control. During the study period, there were 720 patients with ACS, and among them, 216 did not receive tirofiban and 504 patients received tirofiban. Results: ICU stay (days, mean±standard deviation [SD]) for tirofiban group was longer (2.5±0.5) when compared to the controls (1.5±0.5). However, this was not statistically significant. The duration of hospitalization (days, mean±SD) was not significantly different in both groups (6±0.81 vs. 6±0.82). None of the patients developed reinfarction or persistent pain during their stay in the hospital. There were no major adverse events with tirofiban. Conclusion: Therefore, it was concluded that tirofiban does not affect the outcome during hospitalization in patients with ACS.